2013
DOI: 10.1007/s10936-013-9249-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Language Translation Priming Asymmetry with Chinese-English Bilinguals: A Test of the Sense Model

Abstract: The present study aimed to test the Sense Model of cross-linguistic masked translation priming asymmetry, proposed by Finkbeiner et al. (J Mem Lang 51:1-22, 2004), by manipulating the number of senses that bilingual participants associated with words from both languages. Three lexical decision experiments were conducted with Chinese-English bilinguals. In Experiment 1, polysemous L2 words and their L1 Chinese single-sense translation equivalents were selected as primes and targets. In Experiment 2, single-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 23 publications
2
28
1
Order By: Relevance
“…In their classic study with Hebrew-English bilinguals, Gollan, Forster, and Frost (1997) obtained a 53ms cognate priming effect in the L1 to L2 direction, but a non-significant effect in the opposite direction (9ms). This asymmetry is found in other studies (e.g., for Chinese-English: Jiang and Forster 2001;Chen et al 2014; Allen, Conklin, and van Heuven 2015, for Japanese-English cognates).…”
Section: The Question Of Priming Asymmetriessupporting
confidence: 74%
“…In their classic study with Hebrew-English bilinguals, Gollan, Forster, and Frost (1997) obtained a 53ms cognate priming effect in the L1 to L2 direction, but a non-significant effect in the opposite direction (9ms). This asymmetry is found in other studies (e.g., for Chinese-English: Jiang and Forster 2001;Chen et al 2014; Allen, Conklin, and van Heuven 2015, for Japanese-English cognates).…”
Section: The Question Of Priming Asymmetriessupporting
confidence: 74%
“…One thing to note is that several previous studies using an SOA longer than the one used in Experiment 1 of the current study have still reported a null L2-L1 translation priming effect. For example, Xia and Andrews ( 2015 ) found a null L2-L1 translation priming effect in unbalanced Chinese-English bilinguals with moderate to high proficiency in L2 using a 200 ms SOA with 50 ms prime duration (see also Jiang, 1999 ; Jiang and Forster, 2001 ; Witzel and Forster, 2012 ; Chen et al, 2014 ). We propose several possible reasons for this inconsistency.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason might be the number of items used for the experiments. Previous studies reporting a null effect for L2-L1 priming using English-Chinese translation pairs have frequently used fewer than 16 items per cell in a factorial design (e.g., Gollan et al, 1997 ; Jiang, 1999 ; Witzel and Forster, 2012 ; Chen et al, 2014 ; Xia and Andrews, 2015 ; cf. Wang, 2013 ), whereas the current study used 30 items per cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a host of studies now report facilitatory cross-linguistic infl uences for different-script languages as well Sumiya & Healy, 2004 ;Zhang, van Heuven, & Conklin, 2011 ). Across masked priming and translation priming lexical decision and picture-naming tasks, cognate facilitation effects have been found for Greek-French (Voga & Grainger, 2007 ), Korean-English (Kim & Davis, 2003 ), Chinese-English (Chen, Zhou, Gao, & Dunlap, 2014 ), Japanese-English (Allen & Conklin, 2013 ;, and Hebrew-English (Gollan, Forster, & Frost, 1997 ) bilinguals, indicating that the nontarget language can be active despite having a completely different writing system. Interestingly, Table 1 in Schoonbaert, Duyck, Brysbaert, and Hartsuiker ( 2009 ), which quantitates translation priming effects in same-script and different-script bilinguals, suggests that L2-L1 priming may not be as strong in different-script bilinguals as in same-script (see Section 4.2.4.2 ).…”
Section: Cross-linguistic Interactions For Two Languages With Differementioning
confidence: 99%